Workshop “Short Story Writing on Family and Friend Theme” untuk Mengurangi Kecemasan Menulis Berbahasa Asing - Ratri Harida; Rizki Mustikasari; Siti Munifah; Fitriana Kartikasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2024)
EFL learners’ anxiety occurs due to lack of experience and confidence in using the language. Writing short stories can be a medium for conveying moral message, or life values ​​to readers. Steps for writing a short story based on the creative writing process in the Jabrohim Workshop/service training related to knowledge and skills regarding writing short stories in English for students at Madiun Recency attended by 23 students. The workshop